Effect of transforming growth factor beta receptor I inhibitors on myotube formation in vitro - Louise De Saeytyd; Zhihao Wang; Marjon Bloemen; Johannes W. Von den Hoff (Scientific Reports)
Abstract Skeletal muscle injury often occurs after trauma or reconstructive surgery. However, full muscle regeneration is often not achieved because of fibrosis. A key pathway in fibrosis is transforming growth factor ß (TGFß) signaling. Many small molecules that inhibit the TGFß receptor are investigated for their anti-fibrotic activity. However, their effects on myofiber formation are unknown. The aim of this study was to investigate the effect of five transforming growth factor-beta receptor I (TGFßRI) inhibitors on myotube formation in vitro; galunisertib, SM16, AZ12799734, SB431542 and IN1130. First, the toxicity of the inhibitors on C2C12 myoblasts was determined (0-100 µM) as well as their effects on proliferation. Next, the inhibitors (0–20µM) were added to C2C12 cell cultures to determine their effect on myotube formation. Immunofluorescence staining for myosin heavy chain was used to identify myotubes. Data analysis and statistics were performed with Graphpad Prism software. In contrast to galunisertib, AZ12799734 and SB431542, SM16 and IN1130 had no toxic effects. Galunisertib and AZ12799734 were toxic from 10 µM on (p < 0.05) and SB431542 only at 100 µM (p < 0.05). All inhibitors reduced proliferation already at 1 mM. SM16 and IN1130 reduced the fusion index at 1 µM and higher (p < 0.05). SB431542 reduced the fusion index at 5 µM and higher (p < 0.05), and AZ12799734 at 10 µM (p < 0.05) and higher. Only galunisertib had no effect on the fusion index. These results show that galunisertib does not impair the formation of myotubes from C2C12 myoblasts and might be suitable as an anti-fibrotic therapy for muscle regeneration.